Laser-Based Manufacturing II - Antonio Riveiro; Rafael Comesaña; Pablo Pou-Álvarez; Mario González-Quintas; Erik Calvo-García (Journal of Manufacturing and Materials Processing, 2025)
Laser-based manufacturing technologies have consolidated their key position among competitor manufacturing technologies thanks to the elevated level of accuracy, productivity, consistency, and flexibility provided by the advances in laser technology (e [...]